2001
DOI: 10.1116/1.1392402
|View full text |Cite
|
Sign up to set email alerts
|

Impact of nanometer-scale roughness on contact-angle hysteresis and globulin adsorption

Abstract: Besides surface chemistry, the surface roughness on the micrometer scale is known to dominate the wetting behavior and the biocompatiblity properties of solid-state materials. The significance of topographic features with nanometer size, however, has yet to be demonstrated. Our approach is based on well-defined Ge nanopyramids naturally grown on Si(001) using ultrahigh vacuum chemical vapor deposition, where the nanopyramid density can be precisely controlled by the growth conditions. Since the geometry of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
66
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(73 citation statements)
references
References 73 publications
(50 reference statements)
6
66
1
Order By: Relevance
“…Yet, roughness is only a single measure of the topography of a surface, and despite many studies there appears to be no single unifying description of how roughness affects binding (1,2,(52)(53)(54). Our experiments are performed on surfaces with rms roughness between 1.1 nm and 0.18 nm (PD and SCD), considerably smaller than the rms roughness in most other studies (53,55). In addition, the length scale over which the roughness occurs may be important.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, roughness is only a single measure of the topography of a surface, and despite many studies there appears to be no single unifying description of how roughness affects binding (1,2,(52)(53)(54). Our experiments are performed on surfaces with rms roughness between 1.1 nm and 0.18 nm (PD and SCD), considerably smaller than the rms roughness in most other studies (53,55). In addition, the length scale over which the roughness occurs may be important.…”
Section: Discussionmentioning
confidence: 99%
“…Hysteresis is influenced by many factors, including the surface roughness, chemical heterogeneity of the surface, presence of low molecular weight species, and molecular orientation. 49 In a multiphase system advancing contact angle is more sensitive to the low surface energy or hydrophobic domains whereas receding contact angle is more sensitive to the high surface energy or hydrophilic domains. 50 We attribute the increased hysteresis in the POSS containing systems to the surface roughness as well as the chemical heterogeneity imparted by the enrichment of Oib-POSS nanoparticles on the PP surface.…”
Section: Resultsmentioning
confidence: 99%
“…Muller et al showed that an increase in nanometerscale roughness caused a higher rate of IgG (bovine) adsorption on a well defined silicon surface. 52 Adsorption levels on the rougher surface were found to increase above what would be expected given the increase in surface area. The same effect has also been observed in studies of surfaces with nearly-random nanometer-scale roughness, as applied in this study.…”
Section: Effect Of Surface Roughnessmentioning
confidence: 65%